Mapping the Distribution of Organic Matter in Coastal Areas of Banyuwangi Regency - Lestari, Ayu Dewi Puji; Setyaningrum, Ervina Wahyu; Kusuma Dewi, Agustina Tri (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2024)
The Banyuwangi Regency Coastal Area is experiencing an increase in shrimp aquaculture and industrial business activities, which have the potential to cause environmental impacts. It is important to map the distribution of organic matter in coastal waters to address this problem. The main objective of this research is to map the distribution of organic matter in the waters of Banyuwangi Regency. The research method used is a descriptive. The study employed surveys and direct observation as data collection methods, and spatial analysis as the data analysis method. The results showed the mapping of the distribution of organic matter on the coast of Banyuwangi Regency, with the findings of the organic matter content on the Banyuwangi Coast with the lowest value ranging from 2,528 mg/L-9.00 mg/L located in the BL 2, KB 3, BL 3, and BWI 2 areas. The medium distribution value with a value range of 10.724 mg/L-39.18 mg/L is found in the BWI 1, WS 2, WS 1, WS 3, BWI 1, KB 2, KB 1, MC 2 areas. And the highest organic matter distribution value with a value range of 44.24-53.088 mg/L in the KL 2, KL 1, KL 3, BL 1, MC 1 and MC 3 areas. From the distribution results, a mapping picture of the organic matter content in the Banyuwangi Regency Coast is produced.